Overcoming the Problem With Solving Business Problems: Using Theory Differently to Rejuvenate the Case Method for Turbulent Times. (August 2018) - Bridgman, Todd; McLaughlin, Colm; Cummings, Stephen
A questioning of the neoliberal consensus in the global economic order is creating turbulence in Western democracies. Long regarded as the only viable capitalist model, neoliberalism is now subjected to increasing scrutiny. Management education that has been aligned to a neoliberal worldview must now respond to this shifting landscape in order to retain its legitimacy. One core element of management education undergoing revision as a result is the case method of teaching. The case method's traditionally narrow focus on training students to solve business problems is increasingly problematic in an environment where the structure of the capitalist system in which firms operate is now a topic of debate. To address this, we argue for a reconceptualization of the case method's relationship with theory. This has conventionally taken two forms: a hostility to any inclusion of theory in the analytical process and an approach that uses theory as an instrument for profit maximization. We propose an alternative third approach that encourages students to engage in a critical questioning of business-as-usual capitalism from the perspective of multiple stakeholders, including managers, employees, unions, not-for-profit organizations, government, and the natural environment.